2005
DOI: 10.1111/j.1439-0329.2005.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylem dysfunction in Yezo spruce (Picea jezoensis) after inoculation with the blue‐stain fungus Ceratocystis polonica

Abstract: The blue-stain fungus Ceratocystis polonica is pathogenic to Norway spruce (Picea abies) in Europe, as well as to Yezo spruce (Picea jezoensis) and Sachalin spruce (Picea glehnii) in Japan. The wilting mechanism in P. jezoensis saplings after inoculation with C. polonica was examined based on anatomical studies of the phloem and xylem of periodically harvested trees. In addition, the course of sap ascent in the trunks was traced by injection of acid fuchsin solution at harvest. As an initial external symptom, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
4
16
0
1
Order By: Relevance
“…However, following inoculation of host roots, it is clear that significant sapwood damage results from the lesion response, and may lead to significant losses of hydraulic conductivity resulting from tissue occlusion, particularly during periods of strong response. Joseph et al (1998) observed loss of conductivity in roots naturally affected by black-stain root disease and similar findings have been shown experimentally following inoculation of host stems (Kuroda, 2005;Matusick et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, following inoculation of host roots, it is clear that significant sapwood damage results from the lesion response, and may lead to significant losses of hydraulic conductivity resulting from tissue occlusion, particularly during periods of strong response. Joseph et al (1998) observed loss of conductivity in roots naturally affected by black-stain root disease and similar findings have been shown experimentally following inoculation of host stems (Kuroda, 2005;Matusick et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
“…A darkened lesion is commonly observed in conifer hosts around the world following inoculation with ophiostomatoid fungi (Kuroda, 2005;Plattner et al, 2008;Solheim et al, 2001). Increases in oleoresin flow are characteristic in tissues surrounding artificial inoculations (Klepzig et al, 2005;Knebel et al, 2008), particularly following the introduction of highly pathogenic species (Cobb, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Bark beetles are also vectors for bluestaining ascomycete fungi (e.g. Endoconidiophora polonica) (Wingfield et al 1993), which further degrades wood quality (Kuroda 2005). Increasing the stem density and prevalence of mature spruce stands is likely to raise the potential for bark beetle outbreaks (Overbeck and Schmidt 2012).…”
Section: Insect Pests and Pathogensmentioning
confidence: 99%
“…Bark beetles are associated with various species of blue-staining ascomycete fungi that are introduced into the host during an attack (Kirisits, 2010). These blue-stain fungi ultimately grow into the cambium and sapwood of trees, where they occlude the vascular bundles and negatively affect wood quality (Kuroda, 2005). Under severe infestation, this can lead to tree mortality.…”
mentioning
confidence: 99%